THE USE OF BLOCKCHAIN TECHNOLOGY IN LAW, POLITICS AND PUBLIC ADMINISTRATION - Konstantin E Sigalov; Pavel B Salin; Anna S Chuvalnikova (RUDN Journal of Law, 2018)
The article examines the existing practice of using blockchain technology in law, politics and public administration, as well as the prospects of its further use in these areas. The authors approach the problem from the point of view of a systematic approach, which allows to justify the applicability of this technology to solving the problems facing modern law, politics and public administration in a dynamically developing information society. Considering the features of blockchain technology application in each of the three selected areas, the authors establish a pattern according to which the introduction of this technology into the sphere of policy is usually preceded by its introduction into legal and bureaucratic practice. Based on the identified features and patterns of the process of introduction of blockchain technology in law, politics and public administration, the authors analyze the prospects of expanding the scope of this technology in these areas, compare Russian practice with foreign experience.